2019
DOI: 10.1016/j.physletb.2019.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Reliable extraction of the dB(E1)/dE for 11Be from its breakup at 520 MeV/nucleon

Abstract: We analyze the breakup of the one-neutron halo nucleus 11 Be measured at 520 MeV/nucleon at GSI on Pb and C targets within an eikonal description of the reaction including a proper treatment of special relativity. The Coulomb term of the projectile-target interaction is corrected at first order, while its nuclear part is described at the optical limit approximation. Good agreement with the data is obtained using a description of 11 Be, which fits the breakup data of RIKEN. This solves the apparent discrepancy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 34 publications
9
37
0
Order By: Relevance
“…Our results for the cross section of the 11 Be breakup on both targets are in quite good agreement with the GSI data [2,7], as can be seen in Fig. 1.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Our results for the cross section of the 11 Be breakup on both targets are in quite good agreement with the GSI data [2,7], as can be seen in Fig. 1.…”
Section: Resultssupporting
confidence: 90%
“…This quantity has been calculated by theoretical groups and all of them seem to agree with the RIKEN estimate [4,5]. In order to understand this discrepancy and to analyse the GSI data, we present here an eikonal model of the collision, which includes Coulomb and nuclear interactions (and their interference) at all orders as well as relativistic corrections [6,7], coupled with a halo effective field theory (Halo-EFT) structure description of 11 Be [8] which reproduces RIKEN breakup experiment [9].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The Halo-EFT approach [8,9] uses this separation of scale to expand the low-energy behaviour of the 10 Be-n system with R core /R halo ∼ 1/3 as expansion parameter. Following previous works [12,13], we use the Halo-EFT at next-to-leading order (NLO) to construct the c-n potential per partial-wave lJ. We parametrize it as the sum of Gaussians and their derivative…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Since these energies are perfectly suited for the adiabatic approximation, but for the Coulomb interaction, the aforementioned CCE [20,21] is a good starting point for the development of such a model. Recently, it has been shown that treating the nuclear interaction at the Optical Limit Approximation (OLA) of the Glauber model [1,23], and correcting for relativistic effects the sole treatment of the Coulomb interaction in a CCE model, a good agreement with the experimental breakup cross section of 11 Be on Pb measured at 520 MeV/nucleon [9] could be obtained [24]. Figure 5 illustrates this new model applied to the Coulomb breakup of 15 C, measured at GSI at 605 MeV/nucleon [25].…”
Section: Recent Extensions Of the Eikonal Approximation 41 Relativismentioning
confidence: 98%